ENHANCING SOIL WATER HOLDING CAPACITY AND CATION EXCHANGE CAPACITY OF SANDY SOIL WITH APPLICATION OF MANURE ON SIMALINGKAR SOIL - Parlindungan Lumbanraja; Erwin Masrul Harahap (Talenta Publisher, 2015)
The research took place at the University of HKBP Nommensen, Faculty of Agriculture Research Greenhouse in Simalingkar, Medan, Indonesia. It hypothesized that the application of manure as a single factor could increase the soil water holding capacity and soil cation exchange capacity. Research designed with Complete Randomize Design, the treatment replicated by four times. Every parameter that affected significantly will be continued analyzed with Duncan’s Multiple Range Test. For observation had made by measures of soil water holding capacity and soil cation exchange capacity. The concluding of the research can be explained that the effects of manure application on sandy soil after 30 days of incubation at the rate of application equal with 20 t/ha have significantly increased soil water holding capacity only at 72 hours after saturation. The Effects of manure application on sandy soil after 15 as well as 30 days of incubation at all rates of application have not significantly affected cation exchange capacity.